2014
DOI: 10.1001/jamasurg.2014.1627
|View full text |Cite
|
Sign up to set email alerts
|

Mandated Self-reporting of Ventilator-Associated Pneumonia Bundle and Catheter-Related Bloodstream Infection Bundle Compliance and Infection Rates

Abstract: Current mandated self-reported compliance and audit measures are poorly correlated with decreased ventilator-associated pneumonia or catheter-related bloodstream infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The 47 studies that were included reported about the implementation of 49 care bundles. Thirteen studies described the implementation of the central line bundle [ 27 39 ], 27 studies described implementation of the ventilator bundle [ 10 , 16 , 35 , 39 63 ] and nine studies described the sepsis bundle implementation [ 64 72 ] (Additional file 3 ). Two studies reported the implementation of two bundles, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 47 studies that were included reported about the implementation of 49 care bundles. Thirteen studies described the implementation of the central line bundle [ 27 39 ], 27 studies described implementation of the ventilator bundle [ 10 , 16 , 35 , 39 63 ] and nine studies described the sepsis bundle implementation [ 64 72 ] (Additional file 3 ). Two studies reported the implementation of two bundles, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported the implementation of two bundles, i.e. both central line and ventilator bundle [ 35 , 39 ], and two studies were merged because they continued the implementation in the same hospital [ 60 , 61 ]. One study [ 50 ] reported detailed information about the study participants, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to the bundled care processes after the initial focused implementation efforts is often not maintained, or improved as in our study. Helmick and colleagues did report a small increase in compliance in ventilator-associated pneumonia and catheter-related bloodstream infection bundles after initial focused efforts to implement these into routine care [34]. Alternatively, Ferrer et al reported that adherence to a sepsis care bundle returned to baseline 1 year after a national education programme was ceased [35].…”
Section: Discussionmentioning
confidence: 99%
“…recently noted that “current mandated self-reported compliance and audit measures” are poorly correlated with “decreased catheter-related bloodstream infection. [ 4 ]”…”
mentioning
confidence: 99%